Impoliteness Found in I Care a Lot Movie - Made Susini; Ni Ptu Eka Meilinda Yanti; I Made Astu Mahayana (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
The Impoliteness in movies serves as a narrative device to develop characters, create conflict, and reflect real-life social interactions. Applying Culpeper’s impoliteness strategies, this research analyses the strategies, functions, and implications of impoliteness in I Care a Lot movie. The data were taken from the film scripts. The results show that five strategies of impoliteness are found in this movie. They include bald on record impoliteness, positive impoliteness, negative impoliteness, sarcasm or mock politeness, and withhold politeness. Positive impoliteness is the most dominant strategy found in the movie (41.2%). This strategy targets someone's approving face, showing disrespect for something in the interaction. Due to the functions, the most frequent function of impoliteness is coercive impoliteness (58,82%). This indicates that the impolite utterances found in the movie are used to pressure, control, or coerce the interlocutor. The findings suggest that impoliteness in movies is essential in establishing power dynamics and character development. This research contributes to socio-pragmatics by providing insights into how strategies of impoliteness can be applied in communication, including film, to create conflict and tension.